The development of smart home prototypes to control electrical appliances using Blynk application - Mohamad Din, Nur Maizatul Vaneeda; Ab Rahman, Azmanirah; Yusop, Azli (Penerbit UTHM, 2020)
The development of smart home prototype using Blynk application was developed to monitor and control home electrical appliances such as lamps, fans and sockets from a distance. This system is developed for users who always forget to turn off electrical appliances after leaving the house and for disable people using wheelchair. Other than that it is to save the electricity. Six phase in Software Development Life Cycle (SDLC) model was used. The model consist of requirement analysis phase, system design phase, implementation phase, testing phase, application phase and maintenance phase. The prototype was successfully developed. The hardware and software testing analysis on functionality found that all the output working as expected. Graphical User Interface (GUI) development was also created when all the buttons used to control the electrical device on the home prototype could interact well after it was connected to the relay and Nodemcu. Overall, the prototype was successfully fulfilled its required objective.